Development and validation of an ankle brachial index risk model for the prediction of cardiovascular events. (29th August 2020) - Fowkes, FGR; Murray, GD; Butcher, I; Folsom, AR; Hirsch, AT; Couper, DJ; DeBacker, G; Kornitzer, M; Newman, AB; Sutton-Tyrrell, KC; Cushman, M; Lee, AJ; et al.
Abstract: Background: The ankle brachial index (ABI) is related to risk of cardiovascular events independent of the Framingham risk score (FRS). The aim of this study was to develop and evaluate a risk model for cardiovascular events incorporating the ABI and FRS. Design: An analysis of participant data from 18 cohorts in which 24, 375 men and 20, 377 women free of coronary heart disease had ABI measured and were followed up for events. Methods: Subjects were divided into a development and internal validation dataset and an external validation dataset. Two models, comprising FRS and FRS + ABI, were fitted for the primary outcome of major coronary events. Results: In predicting events in the external validation dataset, C-index for the FRS was 0.672 (95% CI 0.599 to 0.737) in men and 0.578 (95% CI 0.492 to 0.661) in women. The FRS + ABI led to a small increase in C-index in men to 0.685 (95% CI 0.612 to 0.749) and large increase in women to 0.690 (95% CI 0.605 to 0.764) with net reclassification improvement (NRI) of 4.3% (95% CI 0.0 to 7.6%, p = 0.050) and 9.6% (95% CI 6.1 to 16.4%, p < 0.001), respectively. Restricting the FRS + ABI model to those with FRS intermediate 10-year risk of 10 to 19% resulted in higher NRI of 15.9% (95% CI 6.1 to 20.6%, p < 0.001) in men and 23.3% (95% CI 13.8 to 62.5%, p = 0.002) in women. However, incorporating ABI in an improved newly fitted risk factor model had a nonsignificant effect: NRI 2.0% (95% CI 2.3 to 4.2%, p = 0.567) in men and 1.1% (95% CI 1.9 to 4.0%, p = 0.483) in women. Conclusions: An ABI risk model may improve prediction especially in individuals at intermediate risk and when performance of the base risk factor model is modest.